Sosialisasi Bullying pada Siswa SDN 1 Pagelaran untuk Menciptakan Sekolah yang Ramah Anak Berbasis Game Edukasi - Dyah Ayu Pramoda Wardhani; Luthfiatus Zuhroh; Wuli Oktiningrum; Adzimatnur Muslihasari; Andi Wibowo (Universitas Islam Raden Rahmat Malang, 2025)
Efforts to socialize bullying at SDN 1 Pagelaran using an educational game-based approach aimed at creating a child-friendly school environment. The research identifies the forms of bullying occurring in the school and its impact on student development. Through the implementation of educational games, students are encouraged to interact positively, recognize and understand the consequences of bullying behavior, and develop empathy and social skills. The results indicate that the use of educational games is effective not only in raising students' awareness about bullying but also in strengthening peer relationships and fostering a more inclusive school atmosphere. Thus, this approach is expected to serve as a model for other schools in addressing bullying issues and supporting healthy and safe learning for all students.